Synthesis of chromatography adsorbent immobilized metal affinity (IMAC) from agarose and effect of the amount of NaBH4 in the derivatization step - Romero, Marcelo Ricardo (2014)
A synthesis of IMAC adsorbent was performed. Agarose matrix was derivatized with epichlorohydrin using different amounts of NaBH4. Furthermore, iminodiacetic acid was immobilized on the modified agarose. Finally, the derivatization efficiency was studied by measuring the epoxide groups and retention of Cu2+. The results indicated that the matrices were modified efficiently and the use of NaBH4 in small amounts is enough to provide a reducing environment to the reaction.